Rainbow magic Bella the bunny fairy - Meadows, Daisy; Ripper, Georgie (Orchard Books London, 2006)
Bella the Bunny Fairy has lost Misty, her magical rabbit, and Jack Frost has sent his goblins to capture the tiny pet! Can Kristy and Rachel help Bella and rescue Misty?